PENTINGNYA PEMULIHAN URINE DARI AIR LIMBAH PERKOTAAN - Bagastyo, Arseto Yekti; Anggrainy, Anita Dwi; Fatkhasari, Yasokhi; Noviani, Riskha (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2022)
Urine contains a high concentration of nutrients that could increase water pollution and corrosion in the sewerage system. Along with the decrease in global phosphorus reserves, this condition may aggravate the worldwide population’s vulnerability in food security, drinking water, sanitation, and hygiene. This paper aims to gain more knowledge on the importance of urine recovery from municipal wastewater. The previous implementation of the urine separation system, the importance of urine diversion, the potential product, and technologies for urine recovery was briefly described. Overall, urine diversion is expected to address those environmental problems by reducing water pollution and organic loading in wastewater treatment plants, providing valuable nutrients for agricultural production, and lessening the economic cost of improper sanitation.